Comparison of pharmacokinetics and stability of generics of cefepime, linezolid and piperacillin/tazobactam with their respective originator drugs: an intravenous bioequivalence study in healthy volunteers. (30th August 2022) - Bergmann, Felix; Wulkersdorfer, Beatrix; Oesterreicher, Zoe; Bauer, Martin; al Jalali, Valentin; Nussbaumer-Pröll, Alina; Wölfl-Duchek, Michael; Jorda, Anselm; Lackner, Edith; Reiter, Birgit; Stimpfl, Thomas; Ballarini, Nicolas; et al.
Abstract: Objectives: The efficacy and quality of generic antibacterial drug formulations are often questioned by both healthcare specialists and patients. Therefore, the present study investigated the interchangeability of generic drugs with their originators by comparing bioequivalence parameters and stability data of generic cefepime, linezolid and piperacillin/tazobactam with their respective originator drugs. Methods: In this open-label, randomized, crossover bioequivalence study, three groups of 12 healthy volunteers each received a single intravenous infusion of either 2 g of cefepime or 4.5 g of piperacillin/tazobactam and two generic formulations, or 600 mg of linezolid and one generic formulation. Plasma sampling was performed, with a 5 day washout period between study days. Stability was tested by storing reconstituted generic and originator products according to their own storage specifications and those of the comparator products. All concentrations were measured by LC-MS. Results: Similar ratios of generic/originator (90% CI) C max were observed for Cefepime-MIP/Maxipime [93.7 (88.4–99.4)], Cefepime Sandoz/Maxipime [95.9 (89.1–103.2)], Linezolid Kabi/Zyvoxid [104.5 (91.1–119.9)], Piperacillin Kabi/Tazobac [95.9 (90.4–101.7)], Piperacillin Aurobindo/Tazobac [99.7 (84.9–104.7)], Tazobactam Kabi/Tazobac [93.4 (87.4–99.8)] and Tazobactam Aurobindo/Tazobac [97.4 (89.7–105.8)]. Accordingly, similar ratios of AUC0– t were observed for Cefepime-MIP/Maxipime [91.1 (87.6–94.8)], Cefepime Sandoz/Maxipime [97.9 (92.5–103.5)], Linezolid Kabi/Zyvoxid [99.7 (93.3–106.6)], Piperacillin Kabi/Tazobac [92.2 (88.3–96.3)], Piperacillin Aurobindo/Tazobac [99.9 (97.0–102.8)], Tazobactam Kabi/Tazobac [91.4 (86.4–96.7)] and Tazobactam Aurobindo/Tazobac [98.8 (94.3–103.6)]. Stable and similar concentrations were measured for all contiguous substances, regardless of storage conditions. Conclusions: Compared with their respective originator drugs, generic cefepime, linezolid and piperacillin/tazobactam met the predetermined bioequivalence criteria. All formulations were stable under the storage conditions of their respective comparators.